Coexisting Situs Inversus Totalis and Immune Thrombocytopenic Purpura - Kemal Gundogdu; Fatih Altintoprak; Mustafa Yener Uzunoğlu; Enis Dikicier; İsmail Zengin; Orhan Yağmurkaya (Case Reports in Surgery)
Situs inversus totalis is a rare congenital abnormality with mirror symmetry of mediastinal and abdominal organs. Immune thrombocytopenic purpura is an autoimmune disease with destruction of thrombocytes. This paper is presentation of surgical approach to a case with coexistence of these two conditions.